Microbiome Modulation as a Novel Strategy to Treat and Prevent Respiratory Infections - Barbara C. Mindt; Antonio DiGiandomenico (MDPI AG, 2022)
Acute and chronic lower airway disease still represent a major cause of morbidity and mortality on a global scale. With the steady rise of multidrug-resistant respiratory pathogens, such as Pseudomonas aeruginosa and Klebsiella pneumoniae, we are rapidly approaching the advent of a post-antibiotic era. In addition, potentially detrimental novel variants of respiratory viruses continuously emerge with the most prominent recent example being severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To this end, alternative preventive and therapeutic intervention strategies will be critical to combat airway infections in the future. Chronic respiratory diseases are associated with alterations in the lung and gut microbiome, which is thought to contribute to disease progression and increased susceptibility to infection with respiratory pathogens. In this review we will focus on how modulating and harnessing the microbiome may pose a novel strategy to prevent and treat pulmonary infections as well as chronic respiratory disease.